Role of the TSPO–NOX4 axis in angiogenesis in glioblastoma - Jiang, Hongxiang; Li, Fei; Cai, Linzhi; Chen, Qianxue (Frontiers in Pharmacology, 2022)
Objective: Angiogenesis is a pathological feature of glioblastoma. Nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) is a vital source of reactive oxygen species (ROS) related to angiogenesis. However, signaling pathways correlated with the isoform oxidase are unknown. The aim of this study was to elucidate the detailed mechanism of the role of NOX4 in angiogenesis in glioblastoma. Methods: Public datasets were searched for studies on immunohistochemistry and western blotting to evaluate NOX4 expression in glioma. The location of NOX4 expression was detected by immunofluorescence. We conducted conditional deletion of the translocator protein (TSPO) targeting the protein with the synthetic ligand XBD173 in the glioblastoma mouse model. NOX4 downregulation was conducted with the NOX4 inhibitor GLX351322, and ROS production and angiogenesis were detected in glioma tissues. Results: Clinical samples and public datasets showed that NOX4 was upregulated and associated with the prognosis. NOX4 is mainly expressed in endothelial cells of glioblastoma. Both TSPO and NOX4 promoted angiogenesis in an ROS-dependent manner, suggesting that TSPO triggered ROS production in glioblastoma via NOX4. Conclusions: These results showed that TSPO is an upstream target of NOX4-derived mitochondrial ROS, which is indispensable for NOX4-derived mitochondrial ROS-induced angiogenesis in glioblastoma. TSPO–NOX4 signaling could serve as a molecular target for therapeutic strategies for glioblastoma.